Research on the Characteristics of Electrolytes in Integrated Carbon Capture and Utilization Systems: The Key to Promoting the Development of Green and Low-Carbon Technologies - Guoqing You; Yunzhi Li; Lihan Dong; Yichun Li; Yu Zhang (Energies)
The core challenge of integrated carbon capture and utilization (ICCU) technology lies in developing electrolytes that combine efficient carbon dioxide (CO2) capture with electrocatalytic conversion capabilities. This review analyzes the structure–performance relationship between electrolyte properties and CO2 electrochemical reduction (eCO2RR), revealing the key regulatory mechanisms. Research shows that the performance of bicarbonate electrolytes heavily depends on the cation type, where Cs+ can achieve over 90% CO selectivity by suppressing the hydrogen evolution reaction (HER) and stabilizing reaction intermediates, though its strong corrosiveness limits practical applications. Although amine absorbents excel in carbon capture (efficiency > 90%), they tend to undergo competitive adsorption during electrocatalysis, making formic acid the primary product (FE = 15%); modifying electrodes with ionomers can enhance their activity by 1.15 times. Ionic liquids (ILs) demonstrate unique advantages due to their tunability: imidazolium-based ILs improve formate selectivity to 85% via carboxylate intermediate formation, while amino-functionalized task-specific ILs (TSILs) achieve a 1:1 stoichiometric CO2 absorption ratio. Recent breakthroughs reveal that ternary IL hybrid electrolytes can achieve nearly 100% CO Faradaic efficiency (FE) through microenvironment modulation, while L-histidine additives boost CH4 selectivity by 23% via interface modification. Notably, constructing a “bulk acidic–interfacial neutral” pH gradient system addresses carbonate deposition issues in traditional alkaline conditions, increasing C2+ product efficiency to 50%. Studies also highlight that cation–anion synergy (e.g., K+/I−) significantly enhances C-C coupling through electrostatic interactions, achieving 97% C2+ selectivity on Ag electrodes. These findings provide new insights for ICCU electrolyte design, with future research focusing on machine learning-assisted material optimization and reactor engineering to advance industrial applications.